THE INFLUENCE OF TIME BUDGET PRESSURE, LOCUS OF CONTROL, AND ORGANIZATIONAL COMMITMENT TO AUDIT QUALITY AND BEHAVIOR OF DYSFUNCTIONAL AUDIT AS INTERVENING VARIABLE (EMPIRICAL STUDY ON AUDITOR BPKP REPRESENTATION OF RIAU PROVINCE) - Rafika Ludmilla; Amir Hasan; Andreas Andreas (Jurnal Ekonomi, 2018)
This study aims to determine the effect of time budget pressure, locus of control, and organizational commitment to audit quality and dysfunctional audit behavior as intervening variables at the auditor of Badan Pengawasan Keuangan dan Pembangunan Riau Province. Using path analysis, 70 auditors working at the Financial and Development Supervisory Board were the respondents in this study.The results show that time budget pressure and locus of control have positive effect on dysfunctional audit behavior and negatively affect audit quality. whereas organizational commitment has a negative effect on dysfunctional behavior of audit and positively influence to audit quality. the implications of this study may be an additional form of useful information as a consideration for the auditor.